Storytelling and Videogames. An interdisciplinary appro- ach to interactive multimedia models for children - Antoniazzi, Anna (Studi sulla Formazione/Open Journal of Education, 2013)
Although scientific literature, since long time, underlines the importance of storytelling and games as essential cognitive and educational moments, current studies and researches are largely resting over a separate analysis of games and storytelling, establishing a hierarchy among them which crowns one or the other likewise from time to time. It is therefore necessary developing and tuning up methods and educational model that will allow us to develop the natural attitude of human mind to place all information inside one context and one set.